HUBUNGAN ANTARA MUTU PELAYANAN FISIOTERAPI DENGAN KEPUASAN PASIEN PADA INSTALASI RAWAT JALAN POLIKLINIK FISIOTERAPI RSUD KABUPATEN WONOGIRI - Niken Isti Rahayu; Mifbakhuddin - (JURNAL LITBANG, 2004)
Result : Mean of quality by, using survey method with explanatory research as o type of research. From patient mean physiotherapy of RSUD Wonogiri counted more or less 300 patient a determined as service is 21,19 and patient sutisfaction 3,73. The performance service quality stdy in category